Pengaruh Pemahaman Perpajakan, Tingkat Pendidikan dan Cinta Uang Terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak (Studi pada Wajib Pajak Orang Pribadi Desa/Kelurahan Mangunjaya Kecamatan Tambun Selatan) - Rohmawati, Afifah; Khasanah, Uswatun; Yuniati, Triana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study explores the influence of Taxation Understanding, Education Level, and Love of Money on Individual Taxpayers' Perceptions of Tax Evasion (a case study on individual taxpayers in Mangunjaya Village, South Tambun District). The aim of this article is to analyze the relationships among the variables examined. The findings reveal that: (1) Taxation understanding positively affects taxpayers' perceptions of tax evasion, (2) Education level does not influence taxpayers' perceptions of tax evasion, and (3) Love of money positively affects taxpayers' perceptions of tax evasion.